Antimicrobial activity of amphiphilic nanomicelles loaded with curcumin against Pseudomonas aeruginosa alone and activated by blue laser light. Issue 3 (18th November 2020) - Rupel, Katia; Zupin, Luisa; Brich, Silvia; Mardirossian, Mario; Ottaviani, Giulia; Gobbo, Margherita; Di Lenarda, Roberto; Pricl, Sabrina; Crovella, Sergio; Zacchigna, Serena; Biasotto, Matteo
Abstract: The aim of this work was to assess the antimicrobial efficacy on Pseudomonas aeruginosa of nanomicelles loaded with curcumin (CUR) alone and activated by blue laser light in an antimicrobial photodynamic therapy (APDT) approach. First, free CUR in liquid suspension and loaded in three amphiphilic nanomicelles (CUR‐DAPMA, CUR‐SPD and CUR‐SPM) were tested both on bacteria and keratinocytes. While free CUR exerted limited efficacy showing moderate cytotoxicity, a strong inhibition of bacterial growth was obtained using all three nanosystems without toxicity on eukaryotic cells. CUR‐SPM emerged as the most effective, and was therefore employed in APDT experiments. Among the three sublethal blue laser (λ 445 nm) protocols tested, the ones characterized by a fluence of 18 and 30 J/cm 2 further decreased the antimicrobial concentration to 50 nM. The combination of blue laser APDT with CUR‐SPM nanomicelles results in an effective synergistic activity that represents a promising novel therapeutic approach on resistant species. Abstract : Antibiotic resistance is a global challenge in modern medicine, as the number of resistant microbial species is constantly increasing, warranting the development of novel strategies. In the present work, a previously known molecule with anti‐microbial properties but poor bioavailability (curcumin) was loaded in three different types of amphiphilic nanomicelles and used in an antimicrobial photodynamic therapy setting with blue laser irradiation on Pseudomonas aeruginosa to improve its effectiveness.